Complex effect of continuous curcumin exposure on human bone marrow‐derived mesenchymal stem cell regenerative properties through matrix metalloproteinase regulation. Issue 1 (26th August 2020) - Yang, Qichen; Leong, Samantha Antonio; Chan, Kwok Ping; Yuan, Xiang‐Ling; Ng, Tsz Kin
Abstract: Curcumin has been reported to be beneficial for cancers, cardiovascular and neurodegenerative diseases, based on its anti‐oxidative, anti‐inflammation, anti‐tumorigenic and neuroprotective properties. With its high‐dose application, curcumin toxicity to systemic tissues is a reasonable concern. Here, we report the responses of human bone marrow‐derived mesenchymal stem cells (hBM‐MSCs) to continuous curcumin exposure. hBM‐MSCs were treated with 0.01‐100 μmol/L curcumin continuously in vitro for 7 days. 25 μmol/L curcumin or above significantly attenuated hBM‐MSC maintenance, whereas 10 μmol/L curcumin reduced hBM‐MSC proliferation and hindered their migration with increasing cell apoptosis. Besides, 5 μmol/L curcumin treatment inhibited hBM‐MSC adipogenic differentiation, but enhanced osteogenic differentiation, which depended on matrix metalloproteinase (MMP)‐13 expression and activity. Furthermore, curcumin treatment reduced MMP1 expression but up‐regulated the immunomodulatory gene IDO1 expression. In summary, this study revealed the complex effects of continuous curcumin exposure on hBM‐MSC maintenance and regenerative properties through MMP regulation. Given the complex effects of curcumin, its use for biomedical purposes should be carefully considered in treatment length and dosage.